Economic value added as an indicator of intellectual capital and its impact on firm performance: the Malaysian evidence - Intan Waheedah; Pok, Wee Ching; Ghazali, Aziatul Waznah (2012)
The conventional accounting standards applied by most of the industrial companies nowadays focus more on the measurement of financial and physical assets, but none on intangible assets. Even the International Accounting Standards (IAS) did not come up with any attempt in redefining the principle, concept and valuation methods particularly for intellectual capital assets. It can be concluded that the eventual published financial statements are of little value to the shareholders due to the deficiency in the recognition on the importance of intellectual capital accounting (Ashton, 2005). The objectives of the study are to assess the role of Economic Value Added (EVA) as an indicator of intellectual capital and to validate the method of EVA to evaluate the impact of intellectual capital on firms' financial performance and stock market performance. Analyses of correlation and simple linear multiple regressions were carried out on the set of variables representing both intellectual capital and firm performance as well as stock market performance. This study contributes to the scarcity, especially in the existing extant of published Malaysian-based literatures, by employing the Economic Value Added (EVA) model approach developed by Joel Stern and G. Bennet Stewart in 1989 as the benchmark indicator in determining the measurement value of intellectual capital. Malhotra (2003) argued that the EVA model approach is effective in presenting intellectual capital in its financial value and practically useful as EVA assist in comparing firm's intellectual capital within the same industry. Applying EVA provide a more straight forward communication in accounting since it is based on accounting rules that have been long established (Sveiby, 2007). Covering a five-year period of study (2006 - 2010), the empirical research investigation will be conducted on all Bursa Malaysia listed companies (except finance sectors). Economic value added - EVA™ method will be adopted in measuring intellectual capital and this is established by the following equation: EVA™ =Net operating profit after tax - [Capital Employed x Weighted Average Cost of Capital]. This study will segregate sample of data into two different groups, firms with positive EVA (value creator) and firms with negative EVA (value destroyer). Results from the analysis show that value creator firms have no significant relationship with either firms' financial performance or stock market performance. However, value destroyer firm have a significant relationship with the Malaysian stock market performance, though do give impact on firms' financial performance.